Media Education Within the National Strategy for Citizenship Education - Elzbieta Malgorzata Bobrowicz-Campos; Armanda Pinto da Mota Matos; Isabel Festas; Ana Maria Seixas (Universidade de Lisboa, 2021)
As a part of the COMEDIG project, this qualitative study aimed to establish to what extent media education content is present in education projects developed by Portuguese schools under the National Strategy for Citizenship Education. Data were gathered from guiding documents provided online by 227 educational establishments that were part of the Project for Autonomy and Curriculum Flexibility in the 2017/2018 academic year. Once identified, media education content was classified into the categories of access and use, critical reading and analysis, and production and expression. Media education activities were referred in guiding documents of 85 establishments; however, only 55 of them considered their implementation under the National Strategy for Citizenship Education. The classification of media education contents, possible in 20 cases, showed the diversity of implementation strategies. These findings suggest that media education is a domain still under construction in Portuguese schools, requiring a more holistic approach.